Исследование методов распознавания изображений в системах технического зрения роботов - Терентьева, С. Г. (ХНУРЭ, 2012)
The report examines the questions of research of methods of image recognition in machine vision systems, robotic systems used in machine building industry. The conducted analysis will allow in practice to choose the best from methods for concrete practical application
Keywords: распознавание изображений; техническое зрение роботов